The principles of structuring the content of the modern textbook on a language of study for educational migrants - Ушакова, Н. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2017)
A textbook shapes the process of communication-oriented language teaching. It is the communicative orientation that determines a structure of the textbook and a study content, which embraces language aspects, i.e. phonetics, vocabulary and grammar, as well as mechanisms for teaching types of speech activity. The article systematizes principles of selection and presentation of phonetic, grammar and vocabulary material in the textbook for educational migrants in accordance with the communicative principle of teaching a non-mother tongue. Selection and structuring of the grammar material is done depending on a field of education. An important role is played by a method of presenting the material: thematic situational or linguistic. Sentence models and a system of structural semantic extenders are used as organizational units for the grammar material. The author substantiates the importance of the pragmatic oriented method of teaching grammar and describes the algorithm of methodical steps when developing the grammar aspect of the textbook. Phonetic means also play an important role in categorization of reality and perform cognitive functions. The process of teaching phonetics includes formation of articulatory, prosodic and intonation skills. The article contains systematized requirements for the bulk of the phonetic material and for a level of phonetic skills for students-philologists and non-philologists, itemizes the main stages of teaching phonetics – introductory, accompanying and correction courses – and their characteristics. The communicative orientation makes the lexical aspect demand a certain compression, and selection of lexical material can be done using thematic-situational organization of the material for non-philologists and an orientation on singling-out three types of relations – paradigmatic, syntagmatic and derivational – for philologists.The author also describes an approach to organize interaction of the above components with the accompanying electronic teaching materials, a methodical basis for complex structuring of the textbook’s content and its electronic supplements intended for students’ independent work.